Recent advances in biodegradable nanocomposites - Pandey, J. K.; Kumar, A. P.; Misra, M.; Mohanty, A. K.; Drzal, L. T.; Singh, R. P. (Journal of Nanoscience and Nanotechnology, 2005)
There is growing interest in developing bio-based products and innovative process technologies that can reduce the dependence on fossil fuel and move to a sustainable materials basis. Biodegradable bio-based nanocomposites are the next generation of materials for the future. Renewable resource-based biodegradable polymers including cellulosic plastic (plastic made from wood), corn-derived plastics, and polyhydroxyalkanoates (plastics made from bacterial sources) are some of the potential biopolymers which, in combination with nanoclay reinforcement, can produce nanocomposites for a variety of applications. Nanocomposites of this category are expected to possess improved strength and stiffness with little sacrifice of toughness, reduced gas/water vapor permeability, a lower coefficient of thermal expansion, and an increased heat deflection temperature, opening an opportunity for the use of new, high performance, lightweight green nanocomposite materials to replace conventional petroleum-based composites. The present review addresses this green material, including its technical difficulties and their solutions.
Keywords: cellulose; layered silicates and properties; Nanocomposite; poly(caprolactone)s; poly(hydroxy alkanoate)s; polyiactic acid; Starch

Photooxidation of vulcanized EPDM/montmorillonite nanocomposites - Morlat-Therias, Sandrine; Fanton, Elisabeth; Tomer, Namrata S.; Rana, Sravendra; Singh, R. P.; Gardette, Jean Luc (Polymer Degradation and Stability, 2006)
The photooxidation of a vulcanized ethylene-propylene-diene monomer (EPDM)/montmorillonite nanocomposite as well as EPDM/nanocomposite with stabilizers was studied under accelerated UV-light irradiation (lambda >= 300 nm, 60 degrees C) for different times. The development of functional groups during oxidation was monitored by infrared spectroscopy. Photodegradation of the neat polymer and composites took place and the increases of absorbance in hydroxyl and carbonyl groups with irradiation times and also the decreases of the EPDM unsaturations were measured. The data indicated that the photooxidation products were not changed in the presence of the nanofiller. However, the presence of MMt was observed to dramatically enhance the rate of photooxidation of EPDM with a shortening of the oxidation induction time, leading to a decrease of the durability of the nanocomposites. On the other hand, it was observed that addition of stabilizers, either Tinuvin P or 2-mercaptobenzimidazole, was efficient in inhibiting the degradative effect of MMt. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EPDM; Nanocomposite; photooxidation rate; stabilization

Single step synthesis and properties of M/MFe2O4 and PVDF/M/MFe2O4 (M = Co, Ni) magnetic nanocomposites - Deka, Sasanka; Joy, Pattayil Alias; Kumar, A. Pratheep (Science of Advanced Materials, 2009)
Metal/ferrite nanocomposites (M/MFe2O4; M = Co, Ni), consisting of nanoparticles of a metal and the corresponding metal ferrite, have been synthesized under in situ conditions by a simple and single step process. The metal/ferrite nanocomposites embedded in a polymer matrix have been prepared by a simple hot-pressing method. The performance parameters such as magnetization, coercivity, permeability and dielectric constant of the two- and three-phase nanocomposite systems are compared. The coercivity increases and the permeability decreases with increasing polymer content in the three-phase composite. Enhancement of the dielectric constant is observed at low frequencies.
Keywords: Dielectric; Ferrite; magnetic properties; Nanocomposite; Nanocrystalline; permeability

Superparamagnetic nanocomposite of magnetite and activated carbon for removal of dyes from waste water - Thakuria, Pankaj; Joy, Pattayil Alias (Nanoscience and Nanotechnology Letters, 2009)
Nanocomposite of superparamagnetic Fe(3)O(4) and activated carbon (AC) is synthesized at room temperature and characterized by various techniques. Magnetic measurements indicated that the Fe(3)O(4) nanoparticles are isolated by the AC particles. The magnetic fluid obtained by dispersion of the nanocomposite in water is found to be relatively stable. The dispersion is found to be very efficient for the removal of methylene blue dye from water. Thus, the nanocomposite is highly suitable for removing dissolved dyes and other contaminants from waste water by a simple magnetic separation process after adsorption on AC.
Keywords: Magnetic Separation; Nanocomposite; Superparamagnetism; Water Purification

Ultrasound assisted synthesis of polyacrylic acid-nanoclay nanocomposite and its application in sonosorption studies of malachite green dye - Sonawane, S. H.; Chaudhari, P. L.; Ghodke, S. A.; Parande, M. G.; Bhandari, Vinay M.; Mishra, Satyendra; Kulkarni, R. D. (Ultrasonics Sonochemistry, 2009)
Synthesis of nanoclay nanocomposite has been undertaken by using polyacryalic acid (PAA) in aqueous medium and ultrasound environment and its application in dye removal has been investigated. The synthesized product was characterized by using FTIR and XRD techniques. The sonosorption capacity of the product namely PAA-nanoclay composite was determined by choosing malachite green (MG) dye as a model pollutant. The effects of various parameters such as nanocomposite loading, pH, various process conditions etc. have been studied. On comparing the results obtained with that of nanoclay as an adsorbent, it was found for an initial concentration of 500 mg/l, the PAA-nanoclay nanocomposite exhibited higher percentage of pollutant removal (68%) and for nanoclay it was 54%. The adsorption data has been correlated using Langmuir and Freundlich models. The fit of the Freundlich isotherm model was found to be good in the entire range of concentration for the experimental sorption data obtained on the nanoclay nanocomposite. A plausible reaction mechanism for use of PAA-nanoclay nanocomposite as ail adsorbent is also proposed. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Malachite Green; Nanocomposite; Polyacrylic acid; Sonosorption; Ultrasound

Preparation and characterization of magnetic nanoparticles embedded in hydrogels for protein purification and metal extraction - Nagireddy, Narayana Reddy; Yallapu, Murali Mohan; Kokkarachedu, Varaprasad; Sakey, Ravindra; Kanikireddy, Vimala; Alias, Joy Pattayil; Konduru, Mohana Raju (Journal of Polymer Research, 2011)
The present work involves the development of hydrogel magnetic nanocomposites for protein purification and heavy metal extraction applications. The magnetic nanoparticles (MNPs) were prepared in situ in poly(acrylamide)-gum acacia (PAM-GA) hydrogels. The formation of magnetic nanoparticles in the hydrogel networks was confirmed by Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD). Scanning electron (SEM) microscopy studies revealed the formation of MNPs throughout the hydrogel networks. The average size of MNPs formed in the hydrogel networks was 3-5 nm as determined by transmission electron microscopy (TEM). The thermal properties of the hydrogel magnetic nanocomposites were evaluated by dynamic scanning calorimetry (DSC) and thermogravimetric (TG) analysis. The magnetic properties of the developed hydrogel magnetic nanocomposites were determined by a vibrating sample magnetometer (VSM). The swelling properties of the hydrogel and the hydrogel magnetic nanocomposites were studied in detail. The hydrogel magnetic nanocomposites are utilized for the removal of toxic metal ions such as Co(II), Ni(II), and Cu(II) and for protein purification. The results confirm that the hydrogel magnetic nanocomposites exhibit superior extraction properties to hydrogels.
International Conference on Advances in Polymer Technology, Cochin Univ Sci & Technol, Cochin, INDIA, FEB 26-27, 2010
Keywords: Bioseparation; Hydrogel; magnetic properties; Metal absorption; Nanocomposite

Synthesis and characterization of CdS/PVA nanocomposite thin films from a complexing agent free system - Saikia, Dulen; Saikia, P. K.; Gogoi, P. K.; Das, M. R.; Sengupta, P.; Shelke, M. V. (Materials Chemistry and Physics, 2011)
CdS/PVA nanocomposite thin films have been deposited on glass substrates by in situ thermolysis of precursors dispersed in polyvinyl alcohol (PVA). The synthetic technique reported in this study is free from complexing agent and hence no need to control the pH of the solution as in the case of conventional CBD. The as-prepared films were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), selected area electron diffraction (SAED), UV-vis spectroscopy, and photoluminescence (PL) spectra. The XRD and SAED results indicated the formation of CdS nanoparticles with hexagonal phase in the PVA matrix. The photoluminescence and UV-vis spectroscopy revealed that CdS/PVA films showed quantum confinement effect. From the shift in optical band gap, particle sizes were calculated using effective mass approximation (EMA) method and it was found to be in agreement with the results obtained from TEM observations. The SEM results indicated that as grown films were homogeneous with no visible pinholes and cracks. The film prepared at 100 degrees C was found to be suitable for application as a window layer in solar cell. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CdS/PVA; Nanocomposite; Optical properties; Thermolysis

Glycolic acid-g-chitosan-gold nanoflower nanocomposite scaffolds for drug delivery and tissue engineering - Kumari, Sangeeta; Singh, Raj Pal (International Journal of Biological Macromolecules, 2012)
This paper reports a simple novel method for the synthesis of flower like gold nanoparticle (three dimensional branched nanoparticle) with >30 tips, under controlled temperature condition. Formation of flower like Au nanoparticle was confirmed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Next step of this paper reveals the potential use of novel hybrids of chitosan-g-glycolic acid and gold nanoflower (AuNF) in controlled drug delivery and tissue engineering applications. The drug loaded novel nanohybrid scaffold is prepared by freeze drying of grafted polymer solution. Grafting of glycolic acid to the chitosan and incorporation of drug were evaluated by Fourier transform infrared spectroscopy (FTIR). The nanohybrid scaffolds were found to be stable towards the pH of the medium. The cell viability study shows that prepared nanohybrid scaffolds are biocompatible. Gold nanoflowers were found to control the drug release rate in the buffer solution (pH 7.4). Therefore, for the glycolic acid grafted chitosan based system, gold nanoflowers are the viable additive for drug delivery. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chitosan; Drug delivery system; Glycolic acid grafting; Gold nanoflower; Nanocomposite

Nanowires of silver-polyaniline nanocomposite synthesized via in situ polymerization and its novel functionality as an antibacterial agent - Tamboli, Mohaseen S.; Kulkarni, Milind V.; Patil, Rajendra H.; Gade, Wasudeo N.; Navale, Shalaka C.; Kale, Bharat B. (Colloids and Surfaces B-Biointerfaces, 2012)
Silver-polyaniline (Ag-PANI) nanocomposite was synthesized by in situ polymerization method using ammonium persulfate CAPS) as an oxidizing agent in the presence of dodecylbenzene sulfonic acid (DBSA) and silver nitrate (AgNO3). The as synthesized Ag-PANI nanocomposite was characterized by using different analytical techniques such as UV-visible (UV-vis) and Fourier transform Infrared spectroscopy (FT-IR), field emission scanning electron microscopy (FE-SEM), thermo gravimetric analysis (TGA). X-ray diffraction (XRD), and transmission electron microscopy (TEM). UV-visible spectra of the synthesized nanocomposite showed a sharp peak at similar to 420 nm corresponding to the surface plasmon resonance (SPR) of the silver nanoparticles (AgNPs) embedded in the polymer matrix which is overlapped by the polaronic peak of polyaniline appearing at that wavelength. Nanowires of Ag-PANI nanocomposite with diameter 50-70 nm were observed in FE-SEM and TEM. TGA has indicated an enhanced thermal stability of nanocomposite as compared to that of pure polymer. The Ag-PANI nanocomposite has shown an antibacterial activity against model organisms, a gram positive Bacillus subtilis NCIM 6633 in Mueller-Hinton (MH) medium, which is hitherto unattempted. The Ag-PANI nanocomposite with monodispersed AgNPs is considered to have potential applications in sensors, catalysis, batteries and electronic devices. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Conducting poly(aniline); In situ polymerization; Nanocomposite

Functional and disordered meso-macroporous gamma-Al2-xMxO3 +/- y (M = Cu and/or Ce) - Gnanakumar, Edwin S.; John, Jino C.; Raja, Thirumalaiswamy; Gopinath, Chinnakonda S. (Journal of Nanoscience and Nanotechnology, 2013)
Disordered meso-macro porous Cu-Ce-Al2O3 nanocomposite (gamma-Al2-xMxO3 +/- y, M = Cu and or Ce) with different compositions has been synthesized. In situ templated sol-gel method has been adopted with simple EDTA ethylenediamine tetra aceticacid and ethylenediamine molecules to prepare gamma-Al2-xMxO3 +/- y, (M = Cu and or Ce). Above meso-macro porous materials were characterized by structural, spectroscopy, microscopy and textural techniques. Detailed characterization indicates that Cu2+ ions are introduced into the ceria and alumina lattice positions. Nano composite nature of the gamma-Al2-xMxO3 +/- y has been confirmed by detailed microscopy investigations. Catalytic activity of the above nanocomposite materials have been screened for environmentally important CO oxidation reaction. 30% Ce-60% Al and 10% Cu containing material shows the best activity among other meso-nnacroporous material with (50%) 100% CO oxidation at (107 degrees C) 145 degrees C.
Keywords: Alumina; CO oxidation; heterogeneous catalysis; Meso-Macroporous Material; Nanocomposite; Sol-gel synthesis

Hollow nanogold/meso-magnetite composite: pulsed laser synthesis, properties, and biosensing application - Chaudhari, Nilima; Warule, Sambhaji; Agrawal, Shailaja; Thakare, Vishal; Jouen, Samuel; Hannoyer, Beatrice; Kale, Bharat; Paknikar, Kishore; Ogale, Satishchandra B. (Journal of Nanoparticle Research, 2013)
A facile and template-free UV (Excimer) laser photolysis process is demonstrated to transform a Fe-complex into unique hollow Fe3O4 nanosphere morphology with each sphere having nanometric pores and an opening. Depending on the Fe-complex concentration and processing time interesting configurations are seen to evolve. When an identical process is applied to a mixture of Fe-complex and chloroauric acid an enthrallingly decorated Au-Fe3O4 nanostructure evolves, with Au nanoparticles surface-loaded on mesospheric Fe3O4. This room temperature process implemented under normal laboratory conditions is clearly versatile and applicable to heterojunction nanomaterials synthesis in a single-step process. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml. The test results demonstrate linear sensing response in the range of 10(3)-10(5) cfu/ml. We also show that these nanostructures can be used for simple electrical conductivity-based biosensing since they show dramatic conductivity change in a simple drop-cast test. A new laser-based approach to the synthesis of unique hollow sphere morphology of magnetite (Fe3O4) without and with Au nanoparticle decoration is presented. The potential application of these gold-decorated magnetic nanostructures was also investigated for immuno-magnetic capture of E. coli in biosensing and these were found to be sensitive even below 1,000 cfu/ml.
Keywords: E. coli cells; Fe-complex; Meso-magnetite; Nanobiotechnology; Nanocomposite; Pulse laser irradiation

Tuning magnetic behavior of nanoscale cobalt sulfide and its nanocomposite with an engineering thermoplastic - Rumale, Narendra; Arbuj, Sudhir S.; Umarji, Govind; Shinde, Manish; Mulik, Uttam P.; Joy, Pattayil Alias; Amalnerkar, Dinesh P. (Journal of Electronic Materials, 2015)
Nanocomposites containing magnetic nanoparticles embedded in a polymer matrix with good thermal stability (up to 200A degrees C) are technologically important. We report an environmentally benign solid-solid approach for synthesis of cobalt sulfide and its nanocomposite using a thermally stable matrix of polyphenylene sulfide. Physicochemical characterizations reveal the formation of nanoclusters of the hexagonal phase CoS. Even though bulk CoS is nonmagnetic, magnetization studies exhibit anomalous magnetic behavior for phase-pure nanoscale CoS and its nanocomposites.
Keywords: Nanocomposite; polyphenylene sulfide; Solid-solid reaction; superparamagnetic

TiO2 modification by gold (Au) for photocatalytic hydrogen (H-2) production - Gupta, Bhavana; Melvin, Ambrose A.; Matthews, Tom; Dash, Sitaram; Tyagi, A. K. (Renewable & Sustainable Energy Reviews, 2016)
TiO2 is indeed one of the widely used semiconductors employed for photocatalytic hydrogen production. Most of its photocatalytic activity-is achieved in its crystalline form. However, its photocatalytic activity is limited to ultraviolet region. For making TiO2 visible light active; Au deposition is strongly recommended due to its surface plasmon feature. Au deposition enhances the photocatalytic activity of both crystalline and nanocrystalline TiO2. Efficiency of photocatalytic activity is controlled by shape and size of Au nanoparticle subsequently the synthetic methodology plays an important role. Herein, we furnish a brief description of TiO2-Au nanocomposite synthesis by different methods viz. sol-gel, photodeposition, deposition-precipitation simple reducing method and dispersion method. A discussion on physical properties of the resultant material is also provided. Three different types of mechanism has been described depending on the type of irradiation and form of TiO2 (crystalline and nanocrytalline). A comparative hydrogen production yield is also tabulated to get an idea about the best synthesis methodology and form of TiO2 for efficient photocatalysis. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Gold nanoparticle; Hydrogen generation; Nanocomposite; Photocatalysis; TiO2

Concurrent synthesis of SnO/SnO2 nanocomposites and their enhanced photocatalytic activity - Roy, Animesh; Arbuj, Sudhir; Waghadkar, Yogesh; Shinde, Manish; Umarji, Govind; Rane, Sunit; Patil, Kashinath; Gosavi, Suresh; Chauhan, Ratna (Journal of Solid State Electrochemistry, 2017)
The SnO/SnO2 nanocomposites were synthesized using semisolvothermal reaction technique. These nanocomposites were prepared using different combination of solvents viz., ethanol, water, and ethylene glycol at 180 A degrees C for 24 h. The synthesized nanocomposites were analyzed with various characterization techniques. Structural analysis indicates the formation of tetragonal phase of SnO2 for the sample prepared in ethanol, whereas for other solvent combinations, the mixture of SnO and SnO2 having tetragonal crystal structures were observed. The optical study shows enhanced absorbance in the visible region for all the prepared SnO/SnO2 nanocomposites. The observed band gap was found to be in the range of 3.0 to 3.25 eV. Microstructural determinations confirm the formation of nanostructures having spherical as well as rod-like morphology. The size of nanoparticles in ethanol-mediated solvent was found to be in the range of 5 to 7 nm. Thermogravimetric analysis indicate the weight gain around 1.3 wt% confirming the conversion of SnO to SnO2 material. The photocatalytic activity of synthesized nanocomposites was evaluated by following the aqueous methylene blue (MB) degradation. The sample prepared in ethylene glycol-mediated solvent showed highest photoactivity having apparent rate constant (K-app) 0.62 x 10(-2) min(-1).
Keywords: Dye-degradation; Nanocomposite; Photocatalysis; tin oxide

Multifunctional inulin tethered silver-graphene quantum dots nanotheranostic module for pancreatic cancer therapy - Joshi, Preeti Nigam; Agawane, Sachin; Agawane, Sachin; Agawane, Sachin; Sarkar, Dhiman; Sarkar, Dhiman (Material Science and Engineering C- Materials for Biological Application, 2017)
Cancer nanotechnology is an emerging area of cancer diagnosis and therapy. Although considerable progress has been made for targeted drug delivery systems to deliver anticancer agents to particular site of interest, new nanomaterials are frequently being developed and explored for better drug delivery efficiency. In the present work, we have explored a novel nanoformulation based on silver-graphene quantum dots (Ag-GQDs) nanocomposite for its successful implementation for pancreatic cancer specific drug delivery in wistar rats. Carboxymethyl inulin (CMI); a modified variant of natural polysaccharide inulin is tethered with the nanocomposite via carbodiimide coupling to enhance the biocompatibility of nanoformulation. Experiments are performed to investigate the cytotoxicity reduction of silver nanoparticles after inulin tethering as well as anticancer efficacy of the system using 5-Fluorouracil (5-FU) as model drug. SEM, TEM, FT-IR, UV-vis, photoluminescence and anti proliferative assays (MTT) are performed for characterisation of the nanocomposite. Hyaluronic acid (HA) is conjugated as targeting moiety for CD-44 (cancer stem cell marker) to fabricate a complete targeted drug delivery vehicle specific for pancreatic cancer. In the present work two prime objectives were achieved; mitigation the toxicity of silver nanoparticles by inulin coating and it's in vivo application for pancreatic cancer. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: acid; Dextran; Drug-delivery; graphene quantum dots; Inulin; Nanocomposite; Nanocomposites; Nanoparticles; Pancreatic Cancer; Silver nanoparticle; Strategies; Systems; Targeted Drug Delivery

TiO2/RGO composites: Its achievement and factors involved in hydrogen production - Gupta, Bhavana; Melvin, Ambrose A. (Renewable &sustainable energy reviews, 2017)
The immense potential shown by TiO2 to participate as a designer material resulting into a new class of high performing photocatalyst has acclaimed it to become an important player in the designing and synthesis of various solar harvesting materials. This role has further been explored by the introduction of graphene into TiO2 matrix. TiO2/reduced graphene oxide (TiO2/RGO) or TiO2/graphene (TiO2/GR) has shown its prospects or relevance to be considered as the next generation photocatalyst for hydrogen production by its reported values in terms of producing hydrogen gas. Hence, there is a requirement of having a detailed up to date write up on the work done in this area in terms of its synthetic procedures, properties and its effect on hydrogen production. Herein, we discuss the different methods involved in the synthesis of such highly efficient materials followed by a brief explanation on its structural and morphological properties. Furthermore, a comparative study on the recent developments in terms of hydrogen evolution efficiency along with a mechanistic approach is also described. Finally, the current challenge and possibility of the future development in this direction is emphasized.
Keywords: Au-tio2 Photocatalysts; Evolution; Generation; graphene; Hydrogen generation; Nanocomposite; Nitrogen-doped Tio2; Photocatalysis; Photocatalytic H-2 Production; Recent Progress; Reduced graphene oxide; TiO2; Tio2-graphene Nanocomposites; Visible-light Irradiation; Water

Sustained release insect repellent microcapsules using modified cellulose nanofibers (mCNF) as pickering emulsifier - Kadam, Sandip L.; Yadav, Prashant; Bhutkar, Siddhant; Patil, Vishal D.; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2019)
We report here an approach to encapsulate N, N-diethyl-3-methylbenzamide (DEET), an insect repellent, through interfacial polycondensation using modified cellulose nanofiber (CNF) as pickering emulsifier. We found that stearic acid functionalized CNF (mCNF) can be used to form stable pickering emulsions (oil-in-oil and water-in-oil), and further encapsulate DEET using interfacial polycondensation with very high encapsulation efficiency of about 98%. Another major advantage of this approach is that mCNF can act both as pickering emulsifier and also strengthen the barrier properties of microcapsules resulting in significant reduction in release rate of DEET. Interpretation of the release profiles using standard mathematical models proposed by Ritger-Peppas show a factor of three reduction in release rate constant for the microcapsules reinforced with mCNF.
Keywords: Cellulose nanofiber; Controlled release; Microcapsules; Nanocomposite; nanoparticle; Pickering emulsion

Nanocomposite of functional silver metal containing curcumin biomolecule model systems: Protein BSA bioavailability - Shedge, Amol A.; Pansare, Shubham V.; Khairkar, Shyam R.; Chhatre, Shraddha Y.; Chakrabarti, S.; Nagarkar, Amit A.; Pansare, Amol V.; Patil, Vishwanath R. (Journal of Inorganic Biochemistry, 2020)
Curcumin, a constituent of Curcuma longa L-Zingiberaceae is used in traditional Indian and worldwide medicine and shows anticancer and antioxidant properties. Curcumin has numerous biological and pharmacological ac-tivities but due to its hydrophobic nature, the major drawback is poor absorption and rapid elimination, rendering curcumin with the tag of a poor biomaterial. Hence, there is a need to develop functional metal containing curcumin model systems (FMCCMS) as a metallo-biomolecule to enhance the bioavailability of curcumin. We designed the interaction of silver metal ion with curcumin to form curcumin-silver nanocomposite (CURC-AgNCP) via ultrasonic synthetic route. Formations of FMCCMS were characterized by spectroscopic techniques. The crystalline face-centered cubic pattern and particle size of the nanocomposite was evaluated using X-ray diffraction and high-resolution transmission electron microscopy. The bonding of silver metal to curcumin was confirmed by X-ray photon spectroscopy. Interaction of the nanocomposite with bovine serum albumin (BSA) protein was performed using excitation, emission, and circular dichroism spectroscopy. In binding interaction of BSA, the negative value of Delta S degrees (-358.04 J mol(-1) K-1) and Delta H degrees (-129.42 KJ mol(-1)) demonstrates the hydrophilic nature of the nanocomposite. The binding distance r evaluated according to the Forster resonance energy transfer theory and was 4.69 nm for CURC-AgNCP, which suggested non-radiative transfer of energy between CURC-AgNCP and BSA. The role of FMCCMS metallo-biomolecule CURC-AgNCP in medicine for cancer activity can have immense importance and hence we performed Sulphorhodamine B based in-vitro cytotoxicity assay on human breast cancer Michigan Cancer Foundation-7 cell line.
Keywords: Ag-based CURC biomaterials; Breast cancer; Metal in medicine; Metallobiomolecules; Nanocomposite

Nonenzymatic glucose detection in human serum using Ni nanoparticles decorated reduced graphene oxide - Waichal, Rupali; Bhirud, Ashwini; Fouad, H.; Gosavi, Suresh; Ashokkumar, Muthupandian (Science of Advanced Materials, 2020)
Reduced Graphene oxide (RGO) decorated with Ni nanoparticles (NiNPs) composites, have been successfully synthesized using a simple hydrothermal method and possessing excellent electrocatalytic activity towards glucose oxidation. The morphological and structural features of RGO-Ni nanocomposites were characterized by field emission scanning electron microscopy (FESEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and energy dispersive spectroscopy (EDS). From TEM, we observed that NiNPs were anchored on RGO sheets. Cyclic Voltammetric (CV) study revealed that the electrocatalytic activity of RGO-Ni nanocomposite with 20% Ni loading (RGONi-20) towards glucose oxidation is better than that shown by bare Glassy Carbon Electrode (GCE), RGO, bare NiNPs, RGONi10 and RGONi-30. The prepared nanocomposites exhibited fast electrocatalytic response (<5 s) towards glucose oxidation. Amperometric study indicates that the present glucose sensor have exhibited excellent performance by offering a lowest detection limit as 5.1 mu M, with linier range from 2 to 5000 mu M and high sensitivity of 896.67 mu A mM(-1) cm(-2). Interference from different anticipatable electroactive substances such as ascorbic acid (AA), uric acid (UA) and dopamine (DA) is not observed. Furthermore, the application of the as prepared sensor was successfully demonstrated for the detection of glucose in human serum and results were comparable to presently used nonenzymatic technique. RGONi-20 nanocomposite electrode holds great promise for the development of biosensors and other electrochemical devices.
Keywords: Electrochemical; Glucose Sensor; Graphene-Nickel Nanoparticles; hydrothermal; Nanocomposite; Nonenzymatic

Sunlight assisted improved photocatalytic degradation of rhodamine B using Pd-loaded g-C3N4/WO(3)nanocomposite - Alman, Vidya; Singh, Kirti; Bhat, Tejasvinee; Sheikh, Arif; Gokhale, Suresh (Applied Physics A-Materials Science & Processing, 2020)
Effective photocatalytic degradation of organic toxic dyes from industrial effluents using low-cost nanomaterials as a photocatalyst under sunlight promises for water purification and environmental recovery. The present work is focused on the synthesis of Palladium (Pd) loaded g-C3N4/WO(3)nanocomposite using a facile method and its photocatalytic degradation of Rhodamine B (RhB) using under sunlight. The results of the photocatalytic dye degradation experiment show that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst degrades 98% of RhB in 40 min of sunlight illumination. This remarkable photocatalytic degradation performance of Pd loaded g-C3N4/WO(3)nanocomposite mainly attributed due to their intrinsic photocatalytic activity and co-existence of enhanced light absorbance and efficient charge transfer process in between the g-C3N4/WO(3)heterojunction. The durability testing experiments indicate that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst could be effectively reused and possesses high photochemical structural stability even after several recycle process. Present experimental results demonstrated highly encouraging photo-degradation response of Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst at outdoor conditions paves the way for the development of energy conversion and environmental remediation process.
Keywords: Nanocomposite; Palladium loading; Photocatalysis; Photodegradation; Rhodamine B; Sunlight

Facile synthesis of nanocomposites of CNF-Sn and C-Sn microspheres: Prospective field emitter - Badadhe, Satish S.; Yadav, Poonam; Suryawanshi, Sachin; More, Mahendra A. (Journal of Alloys and Compounds, 2022)
We report synthesis of Carbon nanofibers (CNFs) and hybrid nanocomposites namely, CNF-Sn and C-Sn microspheres using simple electrospinning technique, followed by annealing in controlled atmosphere. The as-prepared materials were characterized using X-raydiffraction (XRD), Field emission scanning electron microscopy (FESEM), Transmission electron microscopy (TEM), Ultra-violet photoelectron spectroscopy (UPS), and Raman spectroscopy to reveal their physico-chemical properties. As carbon family members are potential materials for field emission (FE) based applications, owing to their high aspect ratio FE characteristics of the synthesized materials were explored at base pressure of 1 x 10(-8) mbar. Interestingly, the hybrid nanocomposite CNF-Sn and C-Sn emitters showed improved FE behavior (with the turn-on field of 3.4 and 1.36 V/mu m, respectively) in contrast to the pristine CNFs emitter (turn-on field of 5.4 V/mu m). Furthermore, the maximum emission current density is substantially enhanced, 7.75 and 4.6 mA/cm(2) for CNF-Sn and C-Sn emitters, respectively. The improvement in the FE behavior of nanocomposite emitters is attributed to the combined effect of morphology and modulation of electronic properties at the interface of nanocomposites. The results confirm that FE characteristics of pristine nanostructures can be greatly improved upon formation of their nanocomposites and this approach can be extended to other nanostructures for improving their multi-functionalities. (c) 2022 Elsevier B.V. All rights reserved.
Keywords: carbon nanofiber; electrospinning; field emission; Nanocomposite; Tin

Novel shear thickening fluids possessing high shear rates using monodispersed silica nanoparticles and PEG - Chavan, Nayaku; Dhage, Atul; Wale, Apparav; Thorave, Asmita; Rajdeo, Kishor; Kamble, Sanjay; Ponrathnam, Surendra; Tambe, Sanjeev; Verma, Sanjeevkumar (Polymer Bulletin, 2023)
Higher shear rate possessing homogeneous shear thickening fluids were synthesized using monodispersed silica nanoparticles and polyethylene glycol (PEG). Novel homogeneous methodology was developed for the synthesis of shear thickening fluids using monodispersed silica nanoparticles and PEG. Shear rate of shear thickening fluids (STF) was determined using rheometer at room temperature. The normal shear rate was observed in the range of 100 to 1200 s(-1), whereas higher shear rate 2000 s(-1) was obtained using monodispersed silica nanoparticles, PEG and shear rate enhancer. Monodispersed silica nanoparticles were synthesized in a typical one-pot using modified Stober's method at room temperature. Precursors were used for the synthesis of monodispersed silica nanoparticles such as tetraethyl orthosilicate (TEOS), ethanol, deionized water and ammonia as catalyst. Particle size of monodispersed silica nanoparticles was in the range of 100-1200 nm, and particle size distribution was varied from 0.000 to 0.221. Synthesis of monodispersed silica nanoparticles was studied by various parameters, namely effect of TEOS concentration, grade of ethyl alcohol, ammonia concentration and water concentration. TEOS concentration effect shows particle size and particle size distribution increases with increase in concentration of TEOS. Even though concentration of TEOS was increased up to 5 times the observation was same for all particle sizes such as 100, 300 and 500 nm. Particularly in the case of 300 nm monodispersed silica nanoparticle synthesis, as TEOS concentration was increased from 1 to 5X (5 times) the particle size was increased from 331.7, 447.8, 497.0, 512.0 and 531.7 nm and particle size distribution was 0.005, 0.000, 0.006, 0.007 and 0.089, respectively. The effect of grade of ethyl alcohol illustrates that Indian rectified spirit shows almost similar results with respect to China make ethyl alcohol. Comparative study of China and Indian rectified spirit shows silica nanoparticle size was 174.6 and 174.2 nm, and particle size distribution was 0.065 and 0.071, respectively. Ammonia concentration effect explains particle size and particle size distribution increases with increase in concentration of ammonia. Water concentration effect shows particle size and particle size distribution increases with increase in concentration of ammonia. Comparative data of water concentration effect for 1316 and 1974 mL shows particle size were 321.7 and 488.0 nm, and particle size distribution was 0.083 and 0.05, respectively, under similar conditions. Morphological studies displayed the shape of the silica nanoparticles was spherical, monodispersed and isolated. A typical TEM image of monodispersed silica nanoparticles for 500 nm was observed with extremely low polydispersity, i.e., 0.000. It is very difficult to get such a type of excellent photograph of monodispersity by Stober's method particularly on large scale. Rheology study of homogeneous shear thickening fluids studied by varying the parameters such as composition of silica nanoparticles with PEG, effect of amount of solvent, effect of refluxing time, effect of additive with respect to the mol. wt. of PEG and effect of additive such as Tannin. All these parameters of STF explored with respect to the shear rate and shear viscosity. Effect of ethanol amount on STF demonstrates the shear rate increases with increase in amount of solvent. Effect of refluxing time on STF exhibits the shear rate increases with increase in refluxing time. Effect of composition based on 500 nm monodispersed silica nanoparticles and PEG 200 with respect to 60:40, 65:35 and 70:30 composition was studied and the results predict that shear rate increases with increase in silica percentage in composition, i.e., 118, 265 and 1200 s(-1) for 60:40, 65:35 and 70:30 composition, respectively, whereas maximum viscosity decreases with increase in silica content, i.e., 2.559, 1.420 and 1.200 Pa.s for 60:40, 65:35 and 70:30 composition, respectively. Effect of additive on shear rate and shear viscosity illustrates that shear rate decreases with increase in additive percentage in composition, whereas maximum viscosity increases with increase in additive content. Effect of additives on shear rate and shear viscosity was performed using 65:35 composition with respect to PEG 200 along with PEG 6000 shows shear rate was decreased from 142 to 6.42 s(-1) and maximum viscosity was increased from 56.1 to 571.0 Pa.s when the quantity of PEG 6000 was doubled. In general, additive decreases shear rate and increases shear viscosity (maximum). But effect of Tannin as an additive on 500 nm monodispersed silica nanoparticles with PEG 200 using 70:30 composition showed enormous increase in shear rate, i.e., 2000 s(-1). This is anomalous behavior of additive was observed.
Keywords: Monodispersed silica nanoparticles; Nanocomposite; Polyethylene glycol; Shear rate; Shear thickening fluid

Polyethylene-grafted sheet-like silsesquioxane nanocomposites with unprecedented adhesion to polar substrates - Sharma, Vivek; Paulbudhe, Uday; Bachhar, Nirmalya; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2023)
Polyethylene is a highly apolar polymer with very pooradhesionto most substrates, necessitating the use of tie layers. Therefore,the synthesis of functional polyethylene is a long-standing challengein catalytic ethylene polymerization. Here, we report the preparationof a nanocomposite comprising polyethylene covalently grafted ontosheet-like silsesquioxanes, with unprecedented adhesion to metal andglass. A norbornene-grafted, layered Mg-silsesquioxane is treatedwith Grubbs second-generation catalyst (G-II), and the identity ofcovalently tethered G-II is unambiguously ascertained. Covalentlytethered G-II catalyzes the ring opening metathesis polymerizationof cyclooctene to poly(cyclooctene). The resulting poly(cyclooctene)is catalytically hydrogenated to yield polyethylene. This polyethylenenanocomposite exhibited a bonding strength of the order of 100 MPaon stainless steel and aluminum, 10-fold higher than reported forengineered polyethylene copolymers. The nanocomposite exhibits anincrease in the polar component of surface energy, yet remains compatibleand cocrystallizes with a polyethylene matrix.
Keywords: adhesion; clay; Nanocomposite; Polyethylene; silsesquioxane

Effect of covalently functionalized Indian bentonite clay on thermal, mechanical strength and morphology structure of extrusion/injection-molded nylon 6 composites - Shanmugam, Kumaresan; Rokade, Dhammaraj S.; Ingole, Pravin G.; Pol, Harshawardhan V.; Arunachalam, Saravanakumar; Bajaj, Hari C. (Polymers for Advanced Technologies, 2024)
The research and development of functional polymer composites and their production have posed significant challenges, particularly in creating high mechanical strength and thermal stability composites. In this study, we utilized a micro corotation extruder and injection molding to produce covalently functionalized Indian bentonite clay-nylon 6 high-strength nanocomposites. For comparison, two different amines, 3-aminopropyl trimethoxysilane and N-[3-(trimethoxysilyl) propyl] ethylene di-amine, were used to functionalize bentonite clay. Additionally, 3% and 5% less amino clay filler was added in the nanocomposite to manufacture the polymer composite. Analytical techniques such as Powder X-Ray Diffraction, Fourier transform infrared, thermal gravimetric analysis, and Brunauer-Emmett-Teller surface area were used to characterize the molecular orientation of amine functionalization on clay minerals. Wide-angle X-ray diffraction, atomic force microscopy, and transmission electron microscope were used to characterize the nylon 6 intercalated in amino clay nanocomposite and the polymer structure morphology. Thermogravimetric analysis and differential scanning calorimetry were used to investigate the crystalline thermal behavior of clay-nylon 6 composites. From the results, it was observed that the composition containing 5 wt.% amino clay demonstrated a significant improvement in tensile strength when compared with the composition containing 3 wt.% amino clay. The mechanical strength and the thermal behavior showed a significant improvement of similar to 200% for 5% amino clay-nylon 6 nanocomposite.
Keywords: amine-functionalized clay; bentonite clay; melt intercalation; Nanocomposite; nylon 6; thermal and mechanical properties

Bifunctional nanoelectrocatalyst: semi-amorphous cobalt tungstate-based nanocomposites surpassing amorphous and crystalline counterparts - Dev, Sahil; Nagappan, Sreenivasan; Kundu, Subrata; Mukherjee, Shatabdi Porel (ACS Applied Materials & Interfaces, 2025)
Electrocatalytic water splitting to hydrogen and oxygen is considered to be one of the significant routes for future renewable energy conversion. Therefore, the development of unique, efficient, and cost-effective bifunctional electrocatalysts, which can perform both hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), is critical for the accessible utilization of renewable energy. The increasing overall efficiency of the water-splitting reaction is pivotal for sustainable energy conversion and hydrogen production. Herein, we present a facile solution-based synthesis route to control the crystallinity of the cobalt tungstate (CoWO4) nanomaterials to amorphous, semiamorphous, and crystalline phases and further exploit these nanomaterials as bifunctional electrocatalysts for the HER, OER, and overall electrochemical water splitting reaction. Notably, the semiamorphous cobalt tungstate nanomaterials show a remarkable surface area of approximately 150 m(2)/g, the highest reported for CoWO4-based materials, and demonstrated superior activity for both the OER and HER and outstanding stability over the amorphous and crystalline counterparts. Notably, the SemiAmp||SemiAmp electrolyzer demonstrated a better performance for overall water splitting than the commercial RuO2||Pt/C electrolyzer.
Keywords: amorphous; CoWO4; electrocatalyst; HER; Nanocomposite; OER; water splitting

Thermal properties of polyethylene-grafted sheetlike silsesquioxanes - Sharma, Vivek; Paulbudhe, Uday; Gupta, Poonam; Zalte, Akshat Shirish; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2025)
Polyethylene-grafted layered silsesquioxanes, termed polyethylene-clays (PEC), are nanocomposites comprising polyethylene chains tethered to inorganic sheets with a phyllosilicate-like structure. Here, we report that these nanocomposites show two-stage crystallization on cooling, qualitatively different from previous reports on polyethylene nanocomposites. We employ differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) to study the melting and crystallization of PEC. End tethering of the polyethylene chains to a nanosheet strongly influences the manner in which PEC crystallizes from the melt on cooling. PEC exhibits two-step crystallization, characterized by a sharp high-temperature exotherm, followed by a broader exotherm at lower temperatures, in contrast to a single sharp exotherm for neat polyethylene. SAXS indicates that lamellar stacks form at high temperatures and that the low-temperature exotherm corresponds to the formation of additional lamellae and their insertion within these stacks. PEC exhibits lower peak melting temperature, lower crystallinity, and a wider melting range relative to polyethylene. We show that the progress of crystallization of PEC is determined by its ultraslow relaxation dynamics. In contrast, PEC in xylene solution exhibits a significantly shorter relaxation time than the melt PEC. Such systems exhibited a single exotherm on cooling and SAXS structure factor peaks with peak positions in a ratio of 1:2. We hypothesize that the high melt viscosity inhibits the crystallization-induced decrease in the specific volume of PEC, resulting in tensile internal stresses that determine the observed thermal behavior.
Keywords: clay; Crystallization; Nanocomposite; Polyethylene; silsesquioxane